Methodology of Calculating Reaction-diffusion Processes with Moving Boundaries of Kinetic Zones - L.M. Musabekova; N.N. Dausheeva; M.A. Jamankarayeva (Chemical Engineering Transactions, 2012)
The main factors which promote arising of kinetic zones with moving boundaries in perfect systems have been considered in our work (Musabekova and Brener, 2004). In this work we submit the methodology for calculating the reaction - diffusion processes in non-perfect mixtures. Two cases, namely, the case of instant chemical reactions and the case of reaction with finite velocity have been considered.